Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1111/j.1439-0507.2003.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Der Basidiomyzet Schizophyllum commune in den Nasennebenhöhlen

Abstract: Zusammenfassung In der medizinischen Literatur der vergangenen 50 Jahre findet man nur 22 Fälle, in denen der weltweit vorkommende Basidiomyzet Schizophyllum commune beschrieben wurde. In einem Zeitraum von drei Jahren haben wir 270 Patienten untersucht, die entweder unter einer chronischen Sinusitis oder unter einer Nasennebenhöhlen‐mykose litten. Dazu wurde entweder Nasenschleim oder Operationsmaterial aus den Nasennebenhöhlen (NNH) kultiviert und die entstandenen Pilzkulturen mikroskopisch identifiziert. Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…ITS1 and ITS2 sequencing confirmed this result. A review of the literature indicated that this identification was quite consistent with previous clinical and mycological reports (3,4,14).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…ITS1 and ITS2 sequencing confirmed this result. A review of the literature indicated that this identification was quite consistent with previous clinical and mycological reports (3,4,14).…”
supporting
confidence: 71%
“…The described clinical manifestations included chronic or allergic sinusitis (3,4,8,13,14), bronchopulmonary involvement (1,5,7,10), fungus ball in the lung (15), ulcerative lesions of the hard palate (12), one atypical meningitidis (2), one brain abscess (11), and one suspected onychomycosis (2). Sinusitis is the most reported feature in S. commune infection, representing half of the cases.…”
mentioning
confidence: 99%
“…Although S. commune is ubiquitous basidiomycous fungus in nature, there were only rare reports of its association with human infections, including those of brain, lung and mouth (6,13). Only 25 cases of sinusitis caused by S. commune have been reported yet (1, 3, 6, 7, 8, 17, 18).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported to be an etiological agent of other types of infections and conditions, such as a brain abscess (16, 17), meningitis (18), an eye infection (19), palate ulceration (20), and onychomycosis (21). Infections have also been reported in other mammals (22-24) and in both immunocompromised and immunocompetent individuals (25,26).The most effective treatment options for infections by S. commune are yet to be determined, although various treatment modalities have been used (14,(25)(26)(27)(28)(29). Most susceptibility patterns for these fungi are restricted to individual cases; however, studies by Gonzalez et al (30) and Chowdhary et al (31) with 5 and 26 strains, respectively, indicated that amphotericin B (AMB), itraconazole (ITC), and voriconazole (VRC) had good in vitro activity against the isolates tested, while elevated MICs were observed for flucytosine and fluconazole.…”
mentioning
confidence: 94%
“…However, it has been reported to be an etiological agent of other types of infections and conditions, such as a brain abscess (16,17), meningitis (18), an eye infection (19), palate ulceration (20), and onychomycosis (21). Infections have also been reported in other mammals (22)(23)(24) and in both immunocompromised and immunocompetent individuals (25,26).…”
mentioning
confidence: 99%